A Trap-Assisted Photomultiplication-Type Organic Photodetector With High Detectivity From Visible to Shortwave Infrared Light - Jingwen Chen; Claire Qing-Ying Huang; Xin Zhang; Sheng Dong; Xiye Yang (IEEE Journal of the Electron Devices Society)
This letter reports a trap-assisted photomultiplication-type organic photodetector (PM-OPD) with a broad sensing range from 400 to 1400 nm. By easily tunning the donor/acceptor ratio in bulk-heterojunction layer consisting Poly([2,6’-4,8-di(5-ethylhexylthienyl)benzo[1,2-b;3,3-b]dithiophene]{3-fluoro-2[(2-ethylhexyl)carbonyl] thieno[3,4-b]thiophenediyl}) (PTB7-Th) and a novel non-fullerene acceptor (NFA) pendant 2,2’-(((2,5-bis(2-octyldodecyl)-3,6-dioxo-2,3,5,6-tetrahydropyrrolo [3,4-c]pyrrole-1,4-diyl)bis(thiophene-5,2-diyl))bis(4-oxonaphthalene-3(4H)-yl-1(4H)-ylidene)) dimalononitrile named DPP-QC, the device shows specifically a high external quantum efficiency (EQE) value of 112% and specific detectivity (D*) over $10^{10}$ Jones at 1200 nm at a light intensity of 0.108 mW/cm2. Meanwhile the PM-OPD shows ultra-fast response time $t_{r}$ and $t_{f}$ of 4.1 $μ $ s and 4.3 $μ $ s on microsecond ( $μ $ s) scale. Our work proves that PM-type shortwave infrared (SWIR) OPD can simultaneously achieve high responsivity, broad-spectral response, fast response and well photodiode characteristics.